DEVELOPMENT OF SWIMMING LEARNING VIDEOS TO IMPROVE BASIC LEVEL TRAINERS - Ato Haryanto; Arifin Z; Azhar Ramadhana Sonjaya (Tadulako Journal Sport Sciences And Physical Education, 2023)
The existence of swimming learning videos is expected to improve basic trainers because basically basic trainers are very difficult to start swimming lessons, so this swimming learning video helps to improve basic trainer abilities. The purpose of this study was to determine the validity and feasibility of swimming learning videos. The method used in this study is a quantitative method because the data obtained is in the form of numbers. While the data collection techniques in this study were through observation, interviews, and questionnaires which were distributed to media experts, subject matter experts and basic trainers. Based on the results of this study, it shows that the answers from all respondents can fulfill the value with a percentage of 87% meaning "Very Eligible". Whereas for the answers of respondents (Material Experts) it produces a validation percentage value of 94% "Very Valid" and for the respondents' answers (Media Experts) it produces a validation percentage value of 85% "Very Valid" so that from the three criteria the respondents' answers can be said to be suitable for use as basic trainer learning media.